Building gender equity from the bottom up in agricultural communities - Gibson, Katherine (Western Sydney University, 2019)
Presented by Katherine Gibson (Western Sydney University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.